The Legal Status of An Individual Company Based On The Copyright Law - Linda Setiawati; Tutiek Retnowati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
One of the relatively dominant business entities in economic activity is the type of business entity in the form of a Limited Liability Company. In the case of sustainable development, one of the establishments of a PT which is establishment of a PT is at least 2 (two) people as stated in Article 7 paragraph (1) of the PT Law. It becomes a problem when a PT arrangement can be establishment by one person and then how is the responsibility for shareholders as in an individual company in the mandate of the Job Creation Act. The formulation of the problem proposed by the author is the legal ratio of individua in the Job Creation Act and the legality of the establishment of a limit liability company. The reseatch conducted by the author uses normative legal research using a staturory approach and a conceptual approach ana historical approach. The result of the discussion area ratio legis the birth pf Company individuals in Indonesia is to provide convenience for the development of micro and small business activities to run their business in the form of a leal entity and the establishment of an individual company in Indonesia is legal and legal if all the procedures for establishment are in accordance with those stipulated in Goverment Regulation 9 of 2021 concering the authorized capital of the company and registration the establishment, amandment, and dissolution of a company that meets criteria for micro and small businesses.